AIR SPRING’S PERFORMANCE IN HEIGHT ADJUSTING FOR BICYCLE SADDLE - FENG RuiLiang; JIANG WeiLiang; ZHU LiPing (Jixie qiangdu)
This paper presents a bicycle saddle height adjustable system,which makes saddle lifted fast. The new system is based on the traditional structure of the bicycle,locates a rigid lockable gas spring under the saddle. Through the gas spring mathematical model,with MATLAB software,obtained the relationship between speed and reaction time,and the displacement curve. Analyzed these variable relationship had made a conclusion that gas spring does it well in lifting the saddle.